2008
DOI: 10.1055/s-2008-1027563
|View full text |Cite
|
Sign up to set email alerts
|

Automated Breast Ultrasound: Lesion Detection and BI-RADS™ Classification – a Pilot Study

Abstract: These preliminary results show that the ABUS allows detection of solid and cystic lesions and their BI-RADS classification with a high reliability in a selected patient group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
1
9

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 12 publications
4
52
1
9
Order By: Relevance
“…Very good agreement regarding BI-RADS classification of HHUS and ABUS (25) as well as only fair agreement has been reported (26). Agreement between mammography and ABUS was poor due to a high percentage of false positive ultrasound interpretations (27).…”
Section: Discussionmentioning
confidence: 98%
“…Very good agreement regarding BI-RADS classification of HHUS and ABUS (25) as well as only fair agreement has been reported (26). Agreement between mammography and ABUS was poor due to a high percentage of false positive ultrasound interpretations (27).…”
Section: Discussionmentioning
confidence: 98%
“…[4][5][6][7][8][9] Recently, an automated breast US system with a highresolution (8 MHz) transducer was introduced. 10 Wenkel et al 10 demonstrated the possibility of using it in the clinical setting for patients with breast lesions. This system is designed to examine patients in the supine position.…”
Section: Introductionmentioning
confidence: 99%
“…Manuel US ile benzer görüntü kalitesi ve tanısal doğruluğa sahiptir. Her iki yöntemle saptanan BI-RADS kategorileri ve kitle saptama oranları benzerdir [28,29]. Yapılan çalışmalarda, bu yöntem ile benign ve malign lezyonların ortaya konmasın-da okuyucular arasında mükemmel uyum bildirilmektedir [28].…”
Section: Taramada Otomatik 3-boyutlu Meme Ultrasonografisiunclassified